Kyle Rote, Jr.'s Complete book of soccer - Rote, Kyle, 1950-; Kane, Basil G (New York : Simon and Schuster, 1978)
A soccer star discusses all aspects of this popular sport, including its history, rules, skills, techniques, strategies, stars, and world records
Includes bibliographical references (page 291) and index
Keywords: Soccer -- United States -- History; Soccer